The climate crisis is here: a primer and call to action for public health nutrition researchers and practitioners in high-income countries. Issue 2 (4th November 2022) - Bell, Brooke M
Abstract: Dietary behaviours and the food systems in which they occur have a significant impact on climate change. The 2022 Intergovernmental Panel on Climate Change (IPCC) reports and other major climate reports have identified population-level dietary shifts towards balanced, sustainable healthy diets as an important mitigation (i.e. prevention) solution for climate change. Thus, public health nutrition researchers and practitioners have a crucial role to play in combatting the climate crisis. They have the content expertise, interdisciplinary training and technical skills needed to facilitate wide-scale dietary behaviour changes at multiple levels of influence and ultimately improve both human and planetary health. This commentary article: (i) summarises how dietary behaviours and food systems contribute to climate change, with a particular focus on high-income countries; (ii) reviews food-system-related climate change mitigation solutions most relevant to public health nutrition researchers and practitioners; and (iii) identifies key gaps in the literature and future research directions for the field.